Respon Pertumbuhan dan Hasil Tanaman Jarak Pagar (Jatropha curcas L.) terhadap Cekaman Kekeringan di Lahan Pasir Pantai pada Tahun Pertama Siklus Produksi - Parwata, I Gusti Made Arya; Indradewa, Didik; Yudono, Prapto; Kertonegoro, Bambang Djadmo; Kusmarwiyah, Rukmini (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACTDevelopment of Jatropha, an important tropical biofuel crop, to coastal sandy soil is an urgent situation due to more limited of fossil fuel in one side, and high potency of coastal sandy land that has not been utilized yet. Tolerant and sensitive genotypes of Jatropha were treated with drought stress using watering interval, and their responds on the vegetative growth and yield were studied in this reasearch. Drought stress significantly decreased all vegetative growth parameters observed, except the number of branch. Different jatropha genotypes had different number of branch, number of leaf, root surface area, total of root length, root diameter, plant dry weight, shoot root ratio and light absorption. IP-1A genotype had the highest yield, i.e 33.54 g of dry seed plant-1 (equal to 0.15 ton ha-1), in the first year.Keywords: biofuel, sand, watering